Menjaga Orang Muda Agar Tetap dalam Pergaulan yang Benar - Alan Hubert Frederik Sanger; Juwinner Dedy Kasingku; Feronika Evlita Siwu (Departement of Mathematics Education, 2023)
Nowadays, the problem that often occurs, including in the religious environment, is a problem related to young people because young people are the biggest target of Satan, so he uses various ways to tempt every young person so that they fall into an unfavorable association so that in the end young people are far from God. That is why it is important for every person to believe that they can protect young people so that they can stay in the right association. This is a qualitative study using library research method. Researchers examine sources by comparing one statements with another taken from articles, books, or information on the internet. In this study, there are several ways to ensure that young people remain in the right associations, among them: understanding correctly what association is, imitating the good associations of several figures in the Bible, and selecting good friends in relationships.